2019
DOI: 10.1111/tbed.13104
|View full text |Cite
|
Sign up to set email alerts
|

Serological evidence of H3N2 canine influenza virus infection among horses with dog exposure

Abstract: Currently, Canine influenza virus (CIV) H3N2 is continuously circulating in dog populations in China, Korea, and the United States (US). Both influenza SA‐α‐2,3‐Gal and SA‐α‐2,6‐Gal receptors have been observed in the respiratory tracts of both horses and dogs. Hence, the increasing number of CIV H3N2 cases in the world indicates a potential risk for transspecies transmission to horses with dog exposure. Here, a seroepidemiological survey of CIV H3N2 infections in horses was conducted using hemagglutination in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, H5N1 remains a strain of concern, having been previously isolated from donkeys during an outbreak [101]. Finally, an immune response to canine H3N2 was previously identified in horses through serology, demonstrating that it may also have the ability to jump species [102].…”
Section: Epidemiology Including Factors Contributing To Local Nationa...mentioning
confidence: 99%
“…In addition, H5N1 remains a strain of concern, having been previously isolated from donkeys during an outbreak [101]. Finally, an immune response to canine H3N2 was previously identified in horses through serology, demonstrating that it may also have the ability to jump species [102].…”
Section: Epidemiology Including Factors Contributing To Local Nationa...mentioning
confidence: 99%
“…Sporadic canine infections with the highly pathogenic avian H5N1 and the swine‐origin A (H1N1) pdm09 viruses have been reported 38,39 . In addition, a previous study showed serological epidemiological evidence of CIV H3N2 infection in horses with exposure to dogs 40 …”
Section: Discussionmentioning
confidence: 98%
“…38,39 In addition, a previous study showed serological epidemiological evidence of CIV H3N2 infection in horses with exposure to dogs. 40 Fortunately, more and more researchers have noticed the potential threat of pets carrying influenza, and there are many studies focusing on the vaccine of canine influenza. 41,42 We hope that more people will pay attention to dog and cat influenza.…”
mentioning
confidence: 99%
“…Cross-species transmission of H3N2 CIV into cats has occurred in Korea and US [74,75]. In a serosurvey of race horses in China, animals in several in riding clubs were positive for H3N2 CIV, with infection being strongly associated with exposure to dogs [76]. To date no natural human infections with either H3N8 or H3N2 CIV have been reported.…”
mentioning
confidence: 99%